Umetna inteligenca v praksi - Bregant, Janez (Analiza (Ljubljana), 2020)
A recent development of artificial intelligence (AI) and its self-evident use in our everyday life have increased interest of the public and experts for all kinds of artificially made autonomous systems. Since AI is not anymore understood merely as a handy tool but also as an independent agent, the question of its impact on our life in terms of morality emerges naturally. Answers to questions such as "Is AI responsible for its actions?", "What are social, legal and cultural consequences of its decisions?", "Should its autonomous models be freely accessible in the market?" etc., determine to a great extent whether AI will be trustworthy in the future or not. The paper introduces five threats associated with our unbridled use of AI and concludes through the analyses of current developments in the fields related to those threats that the society is increasingly becoming a hostage of the AI industry: intelligent systems are not made in a way that they would, while interacting with people, in any of their evolution stages (design, construction, installation and evaluation) respect human rights nor act according to accepted social values.
Keywords: artificial intelligence; človekove pravice; ethics; etika; human rights; machine learning; natural learning processing; obdelava naravnega jezika; strojno učenje; umetna inteligenca